The Wellbeing-Consumption Paradox: A Panel Data Analysis in ASEAN Countries - Anita, Rossy Dwi (Journal of International Conference Proceedings, 2023)
The Esterlin paradox observation shows that income and subjective well-being are correlated at a certain point in time. However, happiness does not increase over a long period of time. On the other hand, income growth is closely associated with an increase in carbon emissions. This leads to risks that drive the climate system to conditions that have consequences for society. This study aims to estimate the relationship between carbon consumption and dimensions of human well-being in ASEAN member states over the period 2014-2021. The relationship between variables is estimated using panel data regression, which shows that carbon consumption has a positive effect on life satisfaction. Meanwhile, GDP per capita is negatively related to life satisfaction. Thus, the Esterlin paradox is still evident to explain the relationship between income and life satisfaction at the country level. The OLS method was run separately to see the influence between variables in a country. Increased carbon consumption in Singapore, Philippines, Laos and Thailand shows a negative relationship with life satisfaction. Meanwhile, the Esterlin paradox is not proven for Singapore and the Philippines.